(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2024)
The writing skill of Baccalaureate students tends to be quite ungrammatical and incoherent, despite of being a key competence in post-compulsory secondary education. This is due to two main factors: the new digital linguistic register, caused by the communicative speed of social media, and the scarce linguistic and orthographic evaluation that academic papers receive from professors. The improvement of students’ orthographic competence can be achieved through the use of didactic resources such as constructive hyperfiction, also known as collaborative writing. This scriptural typology, mediated by the Information and Communication Technologies, allows orthography to be placed at the center of the Teaching/Learning process. In this study, the concept of constructive hyperfiction is theoretically explored in order to subsequently give rise to a range of strategies with which to apply collaborative writing as a didactic resource to improve the spelling skills of Baccalaureate students.